Equality, equity, and the distribution of income - CICARELLI, James S. (Turkish Economic Review, 2025)
The three topics braided together in the title of this paper can be likened, in no particular order, to the elements in Winston Churchill’s classic definition of Russia: a riddle, wrapped in a mystery, insidean enigma. Make no mistake; this is complicated terrain. The purpose of this paper is to add a slight wrinkle to what is already a byzantine subject area. The ultimate goal is to introduce a new way of measuring the distribution of income, an approach that can provide the rationale to actually move the needle of public policy with respect to the issue of income redistribution. The paper begins with an extensive review of ‘equality and the distribution of income’ as the topic has evolved over the past one-hundred plus years, focusing on the Lorenz-curve/ Gini-ratio analysis, the principle measures of income distribution economists use to assess the state of society in terms of equality and inequality. Next follows a discussion, “Equity and the Distribution of Income,” which is a counterpoint to the previous discussion of equality and a prelude to the topic “A Sense of Fairness and the Distribution of Income,” the subject matter of third section of the paper, in which a new approach for assessing the fairness of income distribution is elaborated. The paper concludes with a set of policy implications with respect to income redistribution as implied in the measurement of the distribution of income discussed in the previous section of the paper. Keywords. Equality; Equity; Distribution of income; Lorenz Curve. JEL. D30; D63; E21.